1987
DOI: 10.1093/schbul/13.4.679
|View full text |Cite
|
Sign up to set email alerts
|

Visual Masking and the Schizophrenia Spectrum: Interfacing Clinical and Experimental Methods

Abstract: The present article reviews and evaluates 20 studies of susceptibility to visual masking among individuals within the schizophrenia spectrum using a neurophysiological framework provided by a multichannel model of masking. Particular emphasis is placed upon methodological considerations within the context of the current experimental visual masking literature. While there is ample evidence to suggest that individuals within the schizophrenia spectrum frequently exhibit a backward masking deficit, very little ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 106 publications
(270 reference statements)
1
45
0
Order By: Relevance
“…Consistent with numerous previous studies using similar types of masking tasks, patients with schizophrenia showed impaired detection accuracy only in the longest (317 ms) SOA condition (Balogh and Merritt, 1987;Braff and Saccuzzo, 1981;Braff et al, 1991;Green et al, 1994;McClure, 2001;Miller et al, 1979;Rund et al, 1993). To investigate the role of attentional mechanisms in producing this commonly observed impairment, pupillary responses were recorded as an index of attentional allocation to targets and masks.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with numerous previous studies using similar types of masking tasks, patients with schizophrenia showed impaired detection accuracy only in the longest (317 ms) SOA condition (Balogh and Merritt, 1987;Braff and Saccuzzo, 1981;Braff et al, 1991;Green et al, 1994;McClure, 2001;Miller et al, 1979;Rund et al, 1993). To investigate the role of attentional mechanisms in producing this commonly observed impairment, pupillary responses were recorded as an index of attentional allocation to targets and masks.…”
Section: Discussionsupporting
confidence: 69%
“…When the mask is of similar energy (e.g. duration and luminance) to the target, studies have consistently reported impaired target identification at SOAs of approximately 120-350 ms in medicated and unmedicated, acute and remitted schizophrenia patients in more than 20 studies (Balogh and Merritt, 1987;Braff and Saccuzzo, 1981;Green et al, 1994;McClure, 2001;Miller et al, 1979;Rund et al, 1993). This masking deficit has also been found in schizophrenia-spectrum subjects with schizotypal or psychosis prone traits (Steronko and Woods, 1978;Balogh and Merritt, 1985;Saccuzzo and Schubert, 1981) and in unaffected siblings of schizophrenia patients (Green et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Poor performance on the backward masking task is typically associated with risk for psychosis (Balogh and Merritt, 1987;Green and Nuechterlein, 1999). Transient psychotic states are often present in Borderline Personality Disorder and may be similar to the psychotic features present in the schizophrenia spectrum disorders (Stern, 1938;Frosch, 1964;Kernberg, 1975;Gunderson, 1984;Brodsky et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Degree of disruption in the processing of the target is a function of the temporal delay between the target and the mask (interstimulus interval or ISI). Backward masking performance is typically most impaired when the target and mask are presented contiguously and improves as the onset of the mask is delayed further in time (Braff, 1981 Research on backward masking performance has historically focused on psychotic disorders, where it is a predictor of a vulnerability to schizophrenia (Balogh and Merritt, 1987;Green and Nuechterlein, 1999). However, it is unclear if impaired backward masking is specific to schizophrenia spectrum disorders (Rund et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from standard backward masking paradigms (in which target stimuli are masked) suggests that schizophrenics are particularly vulnerable to masking because they have abnormally persistent or large transient activity (Balogh & Merritt, 1987;Schuck & Lee, 1989). That is, excessive transient activity elicited by the mask would cause a larger than normal masking effect.…”
Section: Introductionmentioning
confidence: 99%